Management of aonla rust (Ravenelia emblicae) using fungicides and biocontrol agents (Indian Journal of Arid Horticulture, 2025)
Studies were conducted to select the effective fungicides and biocontrol agents for the management of Aonla rust. Two spraying of fungicides and biocontrol agents were given at 20 days interval. The results showed that the disease intensity was 18.6% in mancozeb treatment as against 52.4% in the control. This was followed by chlorothalonil (0.2%) and copper oxychloride (0.4%) which recorded 21.4% and 24.3% disease intensity respectively. The second year confirmation trial showed that PDI was low in treatment Chlorothalonil (13.6) followed by Copper oxychloride (17.3), Mancozeb (19.6). In case of bioagents, T. viride recorded PDI of 34.7, Pseudomonas flourescens (27.7) as compared to untreated plants recording PDI of 41.7.
Keywords: biocontrol agents; fungicides; PDI; aonla